The nanostructure’s management is the basis for a functional fatty foods’ production - Ivanov, Sergey; Rashevska, Tamara (My University, 2011)
We were the first who developed the functional types of butter with herbal supplements – such as polysaccharides and cryopowders. Ми були першими, хто розробили функціональні типи масла з рослинними добавками - такими як полісахариди і кріопоршки.
Keywords: butter; nanostructure; вершкове масло; функціональні продукти; наноструктура вершкового масла; кафедра технології молока і молочних продуктів; кафедра експертизи харчових продуктів